Neutron induced reactions at the Athens Tandem accelerator NCSR "Demokritos" - Vlastou, R.; Papadopoulos, C. T.; Kokkoris, M.; Perdikakis, G.; Galanopoulos, S.; Serris, M.; Giantsoudi, D.; Argyropoulos, G.; Kossionides, S.; Harissopulos, S. (HNPS Advances in Nuclear Physics, 2019)
The neutron facility at the 5.5 MV Tandem Tll/25 accelerator of NCSR "Demokritos" has been used to produce monoenergetic neutron beams in the energy range 120-650 keV and 4-11.5 MeV via the 7Li(p,n) and 2H(d,n) reactions, respectively. The flux variation of the neutron beam was monitored by using a BF3 detector, while an investigation of the energy dependence of the neutron fluence has been carried out with a liquid scintillator BC501A detector as well as with the multiple foil activation technique. The 232Th(n,2n)231Th and 241Am(n,2n)240Am as well as (n,2n), (n,p) and (η,α) reactions on natural Ge and Hf isotopes, have been investigated from threshold up to 11.5 MeV, by using the activation method.